Press Freedom in The Digital Era in Indonesia: A Human Rights Perspective - Ari Rama, Bagus Gede (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research discusses press freedom in the digital era in Indonesia from a human rights perspective. With the growth of information and communication technology, especially the internet and social media platforms, access to information becomes easier. However, press freedom often faces challenges such as online censorship and the dominance of major platforms limiting diversity of opinions. The protection of press freedom is regulated in international laws such as the Universal Declaration of Human Rights and the International Covenant on Civil and Political Rights, as well as at the national level by the 1945 Constitution and the Press Law. Efforts to realize press freedom in Indonesia's digital age face challenges from online censorship, restrictions on internet access, and attacks on journalists. The importance of safeguarding press freedom demands cooperation between the government, the media industry, and civil society to ensure the sustainability of democracy. Through regulations that respect human rights and increase public awareness, Indonesia can ensure that press freedom is respected and protected in the digital age.